2012
DOI: 10.1016/j.juro.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Fulguration for Hunner Ulcers: Long-Term Clinical Outcomes

Abstract: Fulguration of Hunner ulcers can be an effective treatment for patients with interstitial cystitis/bladder pain syndrome and focal Hunner ulcers involving less than 25% of the bladder who have symptoms refractory to other therapies. However, a significant subset requires repeat treatment and some patients may even go on to require cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 10 publications
2
58
2
3
Order By: Relevance
“…This retreatment rate is lower than the rates reported by other fulguration studies [16,17]. This may be because 1) the follow-up period of our study was shorter than those of the previous studies, and 2) when symptoms recurred after the first fulguration, we treated them with intravesical instillation; repeat fulguration was applied only if the patient still did not show symptom improvement.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This retreatment rate is lower than the rates reported by other fulguration studies [16,17]. This may be because 1) the follow-up period of our study was shorter than those of the previous studies, and 2) when symptoms recurred after the first fulguration, we treated them with intravesical instillation; repeat fulguration was applied only if the patient still did not show symptom improvement.…”
Section: Discussioncontrasting
confidence: 58%
“…Hillelsohn et al [17] reported the long-term clinical outcomes of 59 patients with HUs who were treated by electrocautery by using the Bugbee electrode. Of the 32 patients who underwent a single fulguration, 25 (78%) reported improved or stable symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…169 Fulguration with a Bugbee electrode is another option that led to symptomatic improvement in 76-90% of 150 cases described. [170][171][172][173] Transurethral coagulation using neodymium:yttrium-aluminum-garnet (Nd:YAG) laser, has been reported in two small observational series with short-term improvements of 78% and 100%. 174,175 To prevent bladder or bowel perforation, low bladder filling volume and low-power setting (10-15 W), firing during 1-3 seconds in constant motion until the ulcer is blanched, are recommended.…”
Section: Treatment Of Hunner's Lesions (Recommended For Patients Withmentioning
confidence: 99%
“…12,13 However, these measures produce only temporary symptom relief in most cases. Progressive deterioration of symptoms refractory to conservative treatment eventually leads to major reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%